Advanced Information Systems Engineering Workshops CAiSE 2011 International Workshops, London, UK, June 20-24, 2011. Proceedings - Salinesi, Camille; Pastor, Oscar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed proceedings of ten international workshops held in London, UK, in conjunction with the 23rd International Conference on Advanced Information Systems Engineering, CAiSE 2011, in June 2011. The 59 revised papers were carefully selected from 139 submissions. The ten workshops included Business/IT Alignment and Interoperability (BUSITAL), Conceptualization of Modelling Methods (CMM), Domain Specific Engineering (DsE@CAiSE), Governance, Risk and Compliance (GRCIS), Integration of IS Engineering Tools (INISET), System and Software Architectures (IWSSA), Ontology-Driven Information Systems Engineering (ODISE), Ontology, Models, Conceptualization and Epistemology in Social, Artificial and Natural Systems (ONTOSE), Semantic Search (SSW), and Information Systems Security Engineering (WISSE).
Keywords: Computer science; Software engineering; Information systems; Artificial intelligence; Management information systems; Computer Science; Information Systems Applications (incl.Internet).; Software Engineering; Business Information Systems; Computer Appl. in Administrative Data Processing; Artificial Intelligence (incl. Robotics).